Prognostic impact of fat tissue loss and cachexia assessed by computed tomography scan in elderly patients with diffuse large B‐cell lymphoma treated with immunochemotherapy. (7th March 2014) - Camus, Vincent; Lanic, Helene; Kraut, Jerôme; Modzelewski, Romain; Clatot, Florian; Picquenot, Jean M.; Contentin, Nathalie; Lenain, Pascal; Groza, Luminata; Lemasle, Emilie; Fronville, Carole; Cardinael, Nathalie; et al.
Abstract Objectives Approximately 30% of DLBCL patients are older than 70 yr. This study evaluated the prognostic impact of a cachexia score (CS) including fat tissue loss (adipopenia) and sarcopenia as assessed by computed tomography (CT scan) in elderly DLBCL patients treated with chemotherapy and rituximab (R). Methods This retrospective analysis included 80 DLBCL patients older than 70 yr treated with R‐CHOP or R‐miniCHOP. Skeletal muscle (SM) and visceral (V) and subcutaneous (S) adipose (A) tissues were measured by analysing CT images at the third lumbar (L3) level. Results The median age of the patients was 78 yr. Forty‐four and 46 patients were considered sarcopenic and adipopenic, respectively. The median progression‐free survival (PFS) was 13.6 months in the adipopenic group and 49.4 months in the non‐adipopenic group [hazard ratio (HR) = 2.27; 95% confidence interval (CI): 1.3–4; P = 0.0042]. The median overall survival (OS) was 25.7 months in the adipopenic group and 57.1 months in the non‐adipopenic group (HR = 1.93; 95% CI: 1.05–3.55; P = 0.0342). A two‐point CS including adipopenia and sarcopenia was created and defined two distinct risk groups with differences in outcomes that were highly significant. The CS was predictive of the prognosis in a multivariate analysis including body mass index (BMI) (< or ≥25 kg/m2), age (< or ≥80 yr), international prognostic index (IPI) and albuminaemia (HR = 3.67; 95% CI = 1.93–6.97; P < 0.0001). Conclusion A CS including sarcopenia and adipopenia, assessed by a single CT scan slice, predicts outcome independent of BMI and the IPI.